London lives: poverty, crime and the making of a modern city, 1690-1800 - Hitchcock, Tim (Cambridge University Press, 2015)
Beggarman, thief, 1690-1713 -- Protest and resistance, 1713-1731 -- Vestries, justices and their opponents, 1731-1748 -- Reformers and their discontents, 1748-1763 -- Finding a voice, 1763-1776 -- The state in chaos, 1776-1789 -- Epilogue, the 1790s